The Advantage of Adopting Risk-Based Internal Auditing in Manufacturing Company - Jeslyn Fedelia; Jennifer Te; Anderson Anderson (LAFADZ JAYA Publisher, 2022)
The activities of a company will continue to change following the changes that occur in the internal environment and the community environment. It will pose a risk and can even be an opportunity for the company to increase its profitability. So from that, all companies including manufacturing companies implement Risk Based Audit (RBA). The purpose of this study is the author will describe what are the advantages of a manufacturing company implementing a risk-based internal audit. The research method used in this study is a qualitative method and secondary data. Risk-based audit is a way or method used in carrying out audit tasks by internal auditors to ensure that existing risks are properly and effectively controlled and managed by company management. In the results of this study, the authors will explain risk-based internal audit in general and the advantages of applying a risk-based audit approach to manufacturing companies.